Viele Ansätze - aber noch kein Duchbruch. Stand und Verbreitung der Elektromobilität im Spätsommer 2017. - Burmeister, Jürgen (DVV Media Group, 2017)
Ein buntes Bild bietet derzeit die deutsche Elektrobus-Landschaft. 35 Unternehmen haben 89 E-Busse verschiedenster Hersteller beschafft, eine Vielzahl jeweils nur ein einziges Fahrzeug. Ebenfalls breit gestreut sind die Hersteller der E-Motoren und Batterien. Zur Anwendung kommen fünf verschiedene Ladetechniken. Eine nächtliche Aufladung ohne Nachladung auf dem Betriebshof beziehungsweise eine Nachladung per auf dem Busdach installierten Stromabnehmer bilden die meisten angewendeten Techniken.

The German electric-bus landscape offers a colorful picture. 35 companies have procured 89 electric busses of various manufacturers, most of them have ordered only one single vehicle each. The manufacturers of electric motors and batteries are widely diversified as well. The German electric-bus landscape offers a colorful picture. 35 companies have procured 89 electric busses of various manufacturers, most of them have ordered only one single vehicle each. The manufacturers of electric motors and batteries are widely diversified as well. Five different charging possibilities come into effect. A nocturnal charging without recharging at the depot or charging via an on-board pantograph are the most applied technologies.
Many approaches - but no national breakthrough.
Keywords: Verkehr; Stadtverkehr; ÖPNV; Busverkehr; Fahrzeug; Elektroantrieb; Energieversorgung; Energiespeicherung; Technikstand; Elektromobilität; Antriebstechnik; Hybridantrieb; Ladetechnik; Batterie